2015
DOI: 10.4103/0972-3919.164016
|View full text |Cite
|
Sign up to set email alerts
|

Role of fluorine-18 fluorodeoxyglucose positron emission tomography in a case of renal cell carcinoma to differentiate tumor thrombus from bland thrombus

Abstract: Tumor thrombus is a rare complication of many solid tumors. We present a case of renal cell carcinoma whose baseline contrast-enhanced computerized tomography (CT) revealed an heterogeneously enhancing mass in the upper half of right kidney with tumor thrombus in the right renal vein extending to suprarenal inferior vena cava (IVC), crossing the cavoatrial junction and reaching up to the right atrium (Grade IV). Fluorine-18 fluorodeoxyglucose (18F-FDG) positron emission tomography (PET)/CT imaging revealed lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In a similar study in the literature for distinguishing benign and malignant tumor thrombus reported 71.4% sensitivity and specificity values of % 90 with SUVmax cut-off value of 3.63, while in another study cut-off value has been reported as 2.25 [14][15][16]. A recent study of 12 patients on the efficacy of FDG PET/CT for assessing the acuity of DVT found similar results with regards to BT with mean SUVmax of 2.41 [17].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In a similar study in the literature for distinguishing benign and malignant tumor thrombus reported 71.4% sensitivity and specificity values of % 90 with SUVmax cut-off value of 3.63, while in another study cut-off value has been reported as 2.25 [14][15][16]. A recent study of 12 patients on the efficacy of FDG PET/CT for assessing the acuity of DVT found similar results with regards to BT with mean SUVmax of 2.41 [17].…”
Section: Discussionmentioning
confidence: 73%
“…TT is mostly an insidental finding in CECT. Tumor thrombus is rarely seen in solid tumors such as mostly in hepatocellular carcinoma (ca) and renal cell ca, followed by ovarian/testicular tumors, colon ca, pancreas ca, lung, breast, thyroid tumors, lymphomas, sarcomas, neuroendocrine tumors [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Maximum standardized uptake value (SUVmax) is semiquantitative parameter that reflect metabolic activity, but is not specific marker of malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FDG PET-CT is a proven procedure in staging, restaging, diagnosis and treatment response in oncological patients. In a recent interesting image report from Sonavane SN et al, the authors reported the imaging findings of a patient with RCC where PET/CT not only ruled out locoregional adenopathy and distant metastases, but also distinguished tumor thrombi from benign thrombi in the same patient (1). In a similar study in the literature for distinguishing benign and malignant tumor thrombus reported 71.4% sensitivity and specificity values of % 90 with SUVmax cut-off value of 3.63, while in another study cut-off value has been reported as 2.25 (2-3).…”
Section: Discussionmentioning
confidence: 99%
“…[21] Furthermore, tumor thrombus has the presence of enhancement, vessel expansion, and uptake of fluorodeoxyglucose on positron emission tomography. [21,22] In our case, a spectral Doppler ultrasound was performed, which was helpful in identifying the IJV filling defect as a malignant lesion because of the presence of vascularity within the IJV thrombus. The presence of vascularity in a thrombus differentiates malignant thrombus from a bland thrombus.…”
Section: Ajsmentioning
confidence: 91%